Attempt to understand the relationship between the water of the soil system and the vegetation: the case of the Martinique lower vegetation floor - JOSEPH, Philippe Leopold (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The soil and water dynamics and the dynamics between soil and vegetation are difficult to explore. Yet plant phenology is closely linked to this interdependence whose characteristics vary with the seasons and the climates as well as the stages of floristic succession. In this area, at the interface between botany, ecology and pedology, the references in the scientific literature are few, particularly concerning the Lesser Antilles where the diversity of floristic assemblages cannot be solely explained by the bioclimates and the topography. By using six stations in the dry sub-humid areas of Martinique and conventional pedology methods we were able to characterise the following descriptors: size, total soil moisture from January 1995 to March 1996, humidity of the different layers and their associated matrix potential (pF) for the same period as well as their porosity volumes. The collected data were used to outline the major functional trends between the floors and the phytocenosis in what regards the water element.